Hubungan Status Gizi, Pemberian ASI Eksklusif, Status Imunisasi Dasar dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Anak Usia 12-24 Bulan di Wilayah Kerja Puskesmas Glugur Darat Kota Medan - Putri Damanik; Mhd.Arifin Siregar; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Acute Respiratory Infections (ARI) incident become the main cause of children under 5 years of age mortality (59%) in developing or development countries. Children under 2 years of age period is critical period of health and golden period of brain development. This research purpose is to find out the correlation of nutritional status, exclusive breastfeeding, basic immunization status with Acute Respiratory Infections (ARI) incident for children age 12 to 24 months in Glugur Darat Public Health Centre at Medan City. This research is observational analytic using case control design. Population is children age 12 to 24 months in Glugur Darat Public Health Centre work area. Sample is taken according the exclusion and inclusion criteria for 30 cases and 30 controls. Data analysis included univariate and bivariate analysis with using chi-square test considering Odds Ratio (OR). Bivariate analysis result with chi-square test show that there is correlation between nutritional status and Acute Respiratory Infections (ARI) incident (p=0.045; OR =3,333), exclusive breastfeeding and Acute Respiratory Infections (ARI) incident (p=0,032; OR=3,2386), basic immunization status and Acute Respiratory Infections (ARI) incident (p=0,037; OR=3,763). It is recommended that the public health center to give implement education about health informations, especially to pregnant and breastfeeding mothers . For mothers is recommended to check frequently or period their children health and growth to posyandu/public health center. For society is recommended to keep environmental sanitation and reduce smoking at the home to prevent children from Acute Respiratory Infections (ARI) incident.